De dynamiek van het gregoriaans. Een onderzoeksperspectief - Hoondert, Martin J. M. (Jaarboek voor liturgieonderzoek, 1999)
Central question in this article is: How did Gregorian chant develop in the Netherlands between 1853 AD and today? During the period from 1853 until 1960 Gregorian chant was closely connected with the context of Catholic movements of restoration, like the general restoration of Catholic life in the Netherlands and the Liturgical Movement. After 1960 there are different contexts of liturgy and church, and the general religious and profane contexts. From a wide, contextual approach we try to picture the development of Gregorian chant. Pillars of our study are three related and interacting perspectives: (1) a broad, contextual approach, (2) the interplay of designation and appropriation, and (3) the problem of (liturgical) inculturation. Closely related with these are two thematic fields: how people are dealing with tradition and the past, and how group identities are discovered and strengthened. This article presents these perspectives and thematic fields and it discusses the different contexts, both diachronically as well as synchronically, in which Gregorian chant has been appropriated.